Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1042/bsr20180551
|View full text |Cite
|
Sign up to set email alerts
|

LIFR-AS1 modulates Sufu to inhibit cell proliferation and migration by miR-197-3p in breast cancer

Abstract: Numerous evidence has recently demonstrated that long non-coding RNAs (lncRNAs) play vital roles in the oncogenesis and development of a wide range of human neoplasms. Leukemia inhibitory factor receptor antisense RNA 1 (LIFR-AS1), a novel cancer-related lncRNA, has been reported to be under-expressed in breast cancer and associated with poor prognosis. However, the exact role of LIFR-AS1 in breast cancer remains largely unclear. The present study aimed to investigate the biological role of LIFR-AS1 in breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 38 publications
(37 reference statements)
0
29
0
Order By: Relevance
“…As expected, the interaction between miR-197-3p and TUSc8 was confirmed by luciferase reporter and RIP assays. According to previous studies, miR-197-3p plays an oncogenic role in breast cancer, bladder cancer and thyroid cancer (19,20,42,43). However, the anti-oncogenic role of miR-197-3p has been found in prostate cancer and gastric cancer (44,45).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As expected, the interaction between miR-197-3p and TUSc8 was confirmed by luciferase reporter and RIP assays. According to previous studies, miR-197-3p plays an oncogenic role in breast cancer, bladder cancer and thyroid cancer (19,20,42,43). However, the anti-oncogenic role of miR-197-3p has been found in prostate cancer and gastric cancer (44,45).…”
Section: Discussionmentioning
confidence: 98%
“…3B). It has been reported that miR-197-3p serves as a tumour promoter in various types of cancer (19,27); thus, miR-197-3p was analysed in subsequent explorations. It was observed that miR-197-3p expression was substantially increased by transfection with miR-197-3p mimic in the MG-63 and U2OS cells (Fig.…”
Section: Tusc8 Is Prominently Downregulated In Os Tissues and Cellsmentioning
confidence: 99%
“…miR-197-3p, as an oncogenic miRNA, has been reported to promote cell proliferation, migration, and invasion in bladder cancer cells [12]. Moreover, LIFR-AS1 inhibits breast cancer cell proliferation and migration by binding to miR-197-3p [13]. In lung cancer cells, the miR-197-3p/p120 catenin axis is regulated by lncRNA MALAT1 to depress chemo-sensitivity [14].…”
Section: Ivyspringmentioning
confidence: 99%
“…A previous study reported that LIFR-AS1 inhibits the proliferation and survival of colorectal cancer cells [10]. Another study demonstrated that LIFR-AS1 has the ability to control breast cancer cell proliferation and migration [11]. However, the role of LIFR-AS1 in NSCLC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are small, endogenous non-coding RNAs that are capable of repressing gene expression by binding to the 3′-untranslated region (3′-UTR) of target mRNAs [10]. Compelling evidence indicates that lncRNAs can work as competitive endogenous RNA (ceRNA) for miRNAs [9,11,12]. For example, the lncRNA MALAT1 antagonizes the activity of miR-199a to promote ZHX1 expression, leading to increased glioblastoma cell proliferation and survival [12].…”
Section: Introductionmentioning
confidence: 99%